A report of the in-farm variation of antimicrobial use in commercial broiler production in Pakistan using an international monitoring system based on treatment frequency - Rehberg, Betty; Brogden, Sandra; Fatima, Fariha; Umair, Muhammad; Hartmann, Maria; Kschonek, Julia; Farooq, Umar; Mohsin, Mashkoor; Kreienbrock, Lothar (Frontiers in Veterinary Science, 2025)
Reducing antimicrobial use (AMU) in animal husbandry is imperative to curb the rising threat of antimicrobial resistance. Therefore, sustainable monitoring of AMU is essential to ensure responsible use, minimize resistance and promote long-term effectiveness. Examining the on-farm AMU in broiler production in Pakistan aimed to encourage farmers to adopt responsible antimicrobial practices, while also helping to observe trends in AMU during the fattening period as well as differences between farms. The data were obtained using the international AMU monitoring system VetCAb-ID (©TiHo Hannover, Germany). In this study, the results of monitoring four commercial broiler farms, each with 20 flocks, were investigated for a period of one year. Treatment frequency (TF) based on Used Daily Dose was used to determine flock, farm and season specific differences in AMU. Describing the relative TF of different antimicrobial classes. Shows that the use of antimicrobial classes varied between farms, among flocks within a farm and across fattening weeks within a flock. Overall, the most frequently used classes were polymyxins (27.2%), fluoroquinolones (20.4%), macrolides (17.1%) and tetracyclines (15.9%). The TF was higher in winter than in summer flocks. A statistically significant difference between summer and winter flocks could be observed in the use of fluoroquinolones (p = 0.0463) and macrolides (p = 0.0325). Using the shared international database VetCAb-ID, detailed and internationally comparable information on the on-farm use of antibiotics in Pakistan broiler production could be obtained and analyzed to identify differences between farms and flocks.